Calling an ambulance for non‐emergency medical situations: Results of a cross‐sectional online survey from an Australian nationally representative sample. (16th September 2022) - Mills, Brennen; Hill, Michella; Miles, Alecka; Smith, Erin; Afrifa‐Yamoah, Eben; Reid, David; Rogers, Shane; Sim, Moira
Abstract: Objective: To investigate the Australian general public's perception of appropriate medical scenarios that warrants a call to an emergency ambulance. Methods: An online survey asked participants to identify the likely medical treatment pathway they would take for 17 hypothetical medical scenarios. The number and type of non‐emergency scenarios ( n = 8) participants incorrectly suggested were appropriate to place a call for an emergency ambulance were calculated. Participants included Australian residents (aged >18 years) who had never worked as an Australian registered medical doctor, nurse or paramedic. Results: From a sample of 5264 participants, 40% suggested calling an emergency ambulance for a woman in routine labour was appropriate. Other medical scenarios which were most suggested by participants to warrant an emergency ambulance call was 'Lego in ear canal' (11%), 'Older person bruising' (8%) and 'Flu' (7%). Women, people aged 56+ years, those without a university qualification, with lower household income and with lower emotional wellbeing were more likely to suggest calling an emergency ambulance was appropriate for non‐emergency scenarios. Conclusions: Although emergency healthcare system (EHS) capacity not increasing at the same rate as demand is the biggest contributor to EHS burden, non‐urgent medical situations for which other low‐acuity healthcare pathways may be appropriate does play a small role in adding to the overburdening of the EHS. This present study outlines a series of complaints and demographic characteristics that would benefit from targeted educational interventions that may aid in alleviating ambulance service attendances to low‐acuity callouts. Abstract :